INTEGRASI SISTEM PENJAMINAN MUTU INTERNAL DALAM MENINGKATKAN STANDAR MUTU PENGELOLAAN PENDIDIKAN DI SEKOLAH - Maulana, Mikail Mega; Suwadi, Suwadi (Idaarah: Jurnal Manajemen Pendidikan, 2024)
This research aims to describe education management standards based on National Education Standards (SNP) and explore the urgency of integrating the Internal Quality Assurance System (SPMI) in education management in schools and madrasas to achieve higher education management quality standards. The method used is a literature study with a qualitative approach, collecting data from relevant literature such as books and journal articles. The research results show that quality standards for education management include aspects of planning, implementation, supervision and evaluation. The implementation of SPMI has proven effective in helping schools and madrasas identify weaknesses in management and take appropriate corrective steps. The SPMI process includes mapping educational quality, determining quality improvement plans, implementing plans, monitoring and evaluating, and establishing new quality standards. By implementing SPMI, schools and madrasas can consistently improve the quality of education, support the achievement of SNP, and build a culture of sustainable quality. This research emphasizes the need for understanding and commitment from all components in schools and madrasas in implementing SPMI to achieve quality education management. This research is limited to a literature study, so it is hoped that future research can use more diverse data collection methods and techniques to expand the analysis from different perspectives.